Perencanaan Dan Perancangan Games Center Di Denpasar, Bali - I Dewa Made Ryan Wijaya Arta Ryan; A.A. Gede Raka Gunawarman; I Gede Surya Darmawan (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2022)
E-sports, is a recreational sport of competitive games, E-sports are starting to be seen by many as an opportunity to become a business or a job. With easy access to the Internet for everyone, teenagers who are still in doubt about their future enjoy playing games in school, it is because they think they can succeed in becoming an E-sports pro gamer without knowing the process required to become a professional E-sports player. Game Center design to meet the needs of the E-sports community space which currently does not exist in Bali to facilitate the community in the form of an E-sports training place or arena. The concept of E-sports Arena will use the concept of the future, in accordance with the function of the building as an E-sports Arena that describes future sports through competitive video games that continue to develop with new technology.